2016
DOI: 10.1186/s12879-016-1700-2
|View full text |Cite
|
Sign up to set email alerts
|

Increase in pertussis cases along with high prevalence of two emerging genotypes of Bordetella pertussis in Perú, 2012

Abstract: BackgroundAs has occurred in many regions worldwide, in 2012 the incidence of pertussis increased in Perú. This epidemiologic situation has been associated with a waning vaccine-induced immunity and the adaptation of Bordetella pertussis to vaccine-induced immunity along with improved diagnostic methods.MethodsThe study comprised a total of 840 pertussis-suspected cases reported in Perú during 2012. We summarize here the distribution of pertussis cases according to age and immunization status along with the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
(38 reference statements)
0
13
1
1
Order By: Relevance
“…Paroxysmal cough and cyanosis were found to be the most frequent and statistically significant symptoms associated with confirmed cases of pertussis herein. However, stridor was not significant in our results, despite being commonly referred to in the literature [24,26].…”
Section: Plos Onecontrasting
confidence: 56%
See 1 more Smart Citation
“…Paroxysmal cough and cyanosis were found to be the most frequent and statistically significant symptoms associated with confirmed cases of pertussis herein. However, stridor was not significant in our results, despite being commonly referred to in the literature [24,26].…”
Section: Plos Onecontrasting
confidence: 56%
“…Considering that non-specific symptoms of pertussis constitute a mandatory notification of a suspected case of pertussis, it is possible that this procedure could introduce bias into the classification of pertussis cases. Moreover, several studies have shown a higher frequency of pertussis in children aged one year or less, mainly those under six months, who present high numbers of hospitalizations and more frequent disease complications [1,13,[24][25][26][27].…”
Section: Plos Onementioning
confidence: 99%
“…Remarkably, cgMLST was much more discriminant than PFGE or MLVA, 2 reference epidemiologic typing methods, which appeared unable to distinguish related intrafamilial isolates or isolates collected from the same patient from cocirculating unrelated ones. PFGE and MLVA are widely used and will likely continue to be used until WGS is largely implemented ( 29 32 ), especially in settings in which WGS cannot be achieved because of cost considerations. Our work provides a correspondence between whole-genome–based phylogenetic data and both PFGE and MLVA genotypes and thus provides essential information for the accurate interpretation of typing data from these legacy typing methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several countries reported an increase of pertussis cases, including Australia, the Netherlands, Spain, Japan, Canada, the USA, Peru and Brazil [11,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%